Electronic Security and Sharia Compliance: Addressing Legal Challenges In Digital Banking In Indonesia - Adzmi, Rifazul; Gustanto, Edo Segara; Rizki Lubis, Rusdi; Gunardi, Setiyawan (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2025)
This study employs a literature-based approach by analyzing academic sources, legal texts, and regulatory documents. The purpose is to examine the legal challenges faced by Islamic banking in Indonesia amid the digital transformation of financial services. Rapid digital developments have reshaped banking services, including Islamic banking. While offering significant opportunities, this transformation also presents complex legal challenges. The study identifies key issues, such as the security of electronic transactions, compliance with digital security standards, personal data protection, and the consistent application of Sharia principles in digital financial innovations. These challenges are further complicated by the need to align them with Indonesia’s legal framework, particularly Law No. 21 of 2008 on Islamic Banking and regulations issued by the Financial Services Authority (OJK). The findings highlight the importance of adaptive legal frameworks and cross-institutional collaboration. Strong coordination among regulators, industry actors, and Sharia scholars is required to establish a digital Islamic banking ecosystem that is both legally sound and compliant with Islamic values.